Analysis and Design of User Interface Private Tutor Mobile Application with Agile System Development Methodologies - Jansen Wiratama; Melody, Michelle; Krisnanto, Obie; Johan, Christian (The Indonesian Journal of Computer Science, 2023)
Wijaya Learning Center in Gading Serpong faced challenges with low course participation due to an inefficient registration system, and to overcome these challenges, a UI analysis and design were conducted, leading to the development of a mobile application. This application allows clients to easily access class information, register online, and make payments. The backend, designed for the owner, supports schedule checks, transaction monitoring, and teacher management tasks. Class schedules, entered by the owner, remain consistent with changes permitted once a month. Clients can select their preferred schedule through the user interface. The study utilized Agile system development methodologies, known for their success in various fields. The research concludes that Agile methodologies significantly streamline the application design process, resulting in a functional mobile application that meets user requirements. Rigorous testing confirms the smooth usability of the application's four main functions, enhancing the private tutoring experience at Wijaya Learning Center.